Obligations and Responsibilities of Notaries in Providing Social Services to The Community as Public Officials - Atmoko, Dwi; Sri Darmadi, Nanang (TABELLIUS: Journal of Law, 2024)
At present, where economic development is increasingly rapid and supported by increasingly developing technology and the increasingly dense population in Indonesia, this country has various and varied problems. Likewise with its diverse society where in reality the economic gap between the able and the unable has its own burden for the person concerned and also the state. In its journey, especially for those who are unable, of course, they also need a notary in achieving their desires, especially regarding the certainty and validity of a letter regarding their assets or related to certain agreements. The role of a notary is needed in society, especially for those who are unable to get their desires for free as mandated in the Notary Law (UUJN) Article 37 paragraph (1) which states that "requires a notary to provide legal services in the notary field free of charge for those who are unable". However, in reality, many notaries do not implement or obey and are trustworthy of the law, which of course is not a good thing. In writing this scientific paper, the author uses a normative legal research method supported by a legislative and historical approach to the formation of notaries and the regulatory norms that surround them. This is done to analyze and see how effective the regulations are for notaries in implementing their functions and performance in providing services to the general public, especially the less fortunate. Notaries in their rights and obligations tend to help people who are able due to economic needs. The honesty and integrity of a notary are questioned in helping people who are unable, where this of course makes it seem as if the notary profession is a profession that is intended for certain people only in this case for people who are able and seem exclusive.